2015
DOI: 10.1515/chempap-2015-0138
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative properties of Sambacus nigra extracts

Abstract: Potential protective effects of elderberry (Sambucus nigra) extracts against oxidative degradation of hyaluronan (HA) were detected in vitro. To induce free-radical-mediated HA degradation, Weissberger's biogenic oxidative system, which mimics the situation of acute inflammation, was applied. Time-and dose-dependent changes of dynamic viscosity of the HA solutions in the presence and absence of two elderberry extracts produced in 2006 and 2012 were recorded by rotational viscometry (RV). Radical scavenging cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Because of its high flavonoid and polyphenolics content, S. nigra has received some attention for its antioxidant properties. Preparations from both S. nigra flowers and fruit have been shown to provide antioxidant effects in vitro, although the extent of this antioxidant activity in vivo is debated, as discussed in the Constituents section of this review in the case of flavonoids in general (Abuja et al, 1998;Cao and Prior, 1999;Pool-Zobel et al, 1999;Youdim et al, 2000;Murkovic et al, 2001;Milbury et al, 2002;Roy et al, 2002;Wu et al, 2002;Lugasi and Hóvári, 2003;Wu et al, 2004;Ginsburg et al, 2004;Nakajima et al, 2004;Lichtenthäler and Marx, 2005;Dawidowicz et al, 2006;Jabłońska-Ryś et al, 2009;Shipp and Abdel-Aal, 2010;Schmitzer et al, 2010;Bratu et al, 2012;Jimenez et al, 2014;Topoľská et al, 2015). S. nigra has also shown promise as a treatment for many other conditions.…”
Section: General Health Propertiesmentioning
confidence: 99%
“…Because of its high flavonoid and polyphenolics content, S. nigra has received some attention for its antioxidant properties. Preparations from both S. nigra flowers and fruit have been shown to provide antioxidant effects in vitro, although the extent of this antioxidant activity in vivo is debated, as discussed in the Constituents section of this review in the case of flavonoids in general (Abuja et al, 1998;Cao and Prior, 1999;Pool-Zobel et al, 1999;Youdim et al, 2000;Murkovic et al, 2001;Milbury et al, 2002;Roy et al, 2002;Wu et al, 2002;Lugasi and Hóvári, 2003;Wu et al, 2004;Ginsburg et al, 2004;Nakajima et al, 2004;Lichtenthäler and Marx, 2005;Dawidowicz et al, 2006;Jabłońska-Ryś et al, 2009;Shipp and Abdel-Aal, 2010;Schmitzer et al, 2010;Bratu et al, 2012;Jimenez et al, 2014;Topoľská et al, 2015). S. nigra has also shown promise as a treatment for many other conditions.…”
Section: General Health Propertiesmentioning
confidence: 99%
“…As the previous data showed that some European elderberries exert antiinflammatory [11], antioxidant [12], antiviral [13], antimicrobial [14], and anticonvulsant [15] activity, the aim of this study was to evaluate biological potential and its correlation with phytochemical composition of fresh elderberry fruits extracts, which were obtained using modern ((MAE), (UAE)) and traditional (maceration (MAC)) extraction techniques. Detailed quantitative and qualitative analysis (LC-MS/MS) of phenolic composition was performed.…”
Section: Introductionmentioning
confidence: 99%
“…In folk medicine, elderberry is used in the treatment of many diseases and ailments thanks to its antioxidant, anticarcinogenic, immune stimulating, antiallergic, antiviral, antibacterial [12,18,28], antidepressant and hypoglycemic properties, as well as the ability to reduce body fat and blood lipid concentrations [12]. Elderberry flowers can be used both for prevention and therapy of a wide array of diseases due to immunomodulatory [42,43], antiinflammatory [44][45][46], antioxidant [28,[47][48][49][50], antimicrobial [12,51,52] and antiviral [41,53,54] activities. In vitro experiments demonstrated the ability of elderberry extract or its constituents to suppress proliferation and viability of various cancer cell lines [25,33,[55][56][57][58] and to prevent angiogenesis in tumor [55,59].…”
Section: Physiological and Therapeutic Actions Of Elderberry And Its ...mentioning
confidence: 99%
“…Reduction in the intracellular reactive oxygen species (ROS) production [46,66] Water elderberry fruit extract Weissberger's biogenic oxidative system Inhibition of oxidative degradation of hyaluronan (HA); ability to scavenge free radicals [50] Table 1. Cont.…”
Section: Human Intestinal Epithelial Cells Caco-2 and Human Skin Kera...mentioning
confidence: 99%